Addressing spirituality and spirituality needs in medical imaging - Zainuddin, Zainul Ibrahim (2014)
Spirituality and spiritual needs in healthcare are receiving attention and has been accepted as part of patient centered care. There are ample evidences from the western literature to denote the importance and relevance of addressing spirituality and spiritual needs by clinicians and nurses. Predominantly, the discussions involve aspects that are related to death, euthanasia or end of life; areas not normally encountered by Medical Imaging practitioners in their professional settings. The lack of spirituality and spiritual needs being discussed in the field of Medical Imaging could effectively distance this group of practitioners from an important component in the holistic approach in patient care. This presentation attempts to fill this gap by benefitting from the evidences from existing literatures. They were used to align possible areas within the macro and micro components in Medical Imaging practice where spirituality and spiritual needs can be addressed. Patient-practitioner interaction, inter -practitioner interaction, the management, the technologies and the procedures are some of the macro components examined for possible alignments. While, the concept of principles and objectives of healthcare, the rights of the patients, and preserving the concept of dignity are viewed within a spiritual framework. Some scenarios where spirituality and spiritual needs can be introduced in Medical Imaging are highlighted. Anticipated challenges, obstacles and issues pertaining to addressing spirituality and spiritual needs within each macro and micro component are also given the necessary attention. One particular issue worth mentioning is the reservations towards discussing spiritual matters in the Medical environment. Suggestions were made to promote, enhance and sustain spirituality and spiritual needs within the given practice. The presentation also pays particular attention in discussing the two components, bearing in mind the multi-religious composition of the Malaysian population. Hopefully this paper can trigger further discourses in adopting and adapting spirituality and spiritual needs within the Medical Imaging practice. This can be taken as another step towards achieving excellence in the service. Furthermore it can help to redefine the role of the Medical Imaging practitioner in positioning the relevance of their profession in healthcare.